Method for improving interface bonding strength of metal-polymer composite structure
By blanching the surface of the titanium alloy and laser etching to form a microtexture, and filling the polymer PLA material into the microtexture with 3D printing technology, the problem of low bonding strength of the metal-polymer composite structure interface is solved, and efficient and environmentally friendly bonding strength is achieved.
Patent Information
- Application Number
- CN202411877326.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The interface bonding strength of the metal-polymer composite structure is low, and the existing connection methods have problems of local stress concentration, long curing time, easy aging, and low efficiency.
Microtexture is formed by blanching the surface of the titanium alloy and laser etching, and the polymer PLA material is filled into the microtexture in combination with 3D printing technology to form a mechanical occlusal connection.
The interface bonding strength of the metal-polymer composite structure is significantly improved, and the local stress concentration is avoided. The process is simple and easy to implement, and it is green and environmentally friendly. The bonding strength can be increased to 7.1 MPa.
Smart Images

Figure CN119734439A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dissimilar material connection, and in particular to a method for improving the interface bonding strength of a metal-polymer composite structure. Background Art
[0002] As the demand for lightweight structures in advanced manufacturing industries such as automobiles, rail transit, and aerospace gradually increases, the connection of heterogeneous lightweight materials has become a hot spot for achieving lightweight. By combining plastics and metals, heterogeneous structures can have both lightweight and high-strength and impact-resistant properties, and high-quality connection of the two materials can be achieved, which has great advantages and application prospects for achieving lightweight.
[0003] Metal-polymer composite structures can achieve lightweight equipment while maintaining high mechanical properties. However, the differences in the physical and chemical properties of metals and polymers make it very difficult to connect the two. At present, the main methods of metal-polymer connection are mechanical connection, adhesive connection and welding, but they all have certain problems. For example, in mechanical connection, bolt connection and riveting have the problem of local stress concentration, adhesive connection has the problem of long curing time, easy aging and low efficiency, and welding has the problem of interface defects, resulting in low metal-polymer interface bonding strength. Therefore, exploring methods to improve the metal-polymer interface bonding strength has important application value.
[0004] In view of this, it is necessary to design a method to improve the interface bonding strength of the metal-polymer composite structure to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the interface bonding strength of the metal-polymer composite structure by utilizing laser etching and fused deposition modeling (FDM) 3D printing technology to significantly improve the interface bonding strength between the titanium alloy TC4 and the polymer PLA, thereby avoiding local stress concentration at the interface.
[0006] To achieve the above-mentioned object of the invention, the present invention provides a method for improving the interface bonding strength of a metal-polymer composite structure, comprising the following steps: S1, performing a texturing treatment on the surface of the titanium alloy to obtain a texturized titanium alloy; S2, performing laser etching on the surface of the roughened titanium alloy obtained in step S1 to form a micro texture on the surface of the titanium alloy, wherein the line spacing of the laser is 0.01-0.15 mm when etching the micro texture; S3. Use 3D printing to print polymer PLA material on the surface of titanium alloy etched with micro-texture, so that polymer PLA is filled into the micro-texture to form a mechanical bite connection, and obtain a metal-polymer composite structure.
[0007] As a further improvement of the present invention, in step S1, the texturing treatment is specifically to texturize the surface of the titanium alloy by mechanical sandblasting.
[0008] As a further improvement of the present invention, in step S2, the line spacing of the laser etching is 0.05-0.15 mm.
[0009] As a further improvement of the present invention, in step S2, the micro texture is a structure in which grooves and pits are arranged alternately.
[0010] As a further improvement of the present invention, the width of the groove and the diameter of the pit are both 40-60 μm.
[0011] As a further improvement of the present invention, the spacing between the groove and the adjacent pit is 0.8-1.2 mm.
[0012] As a further improvement of the present invention, the pits are arranged at intervals along a direction parallel to the grooves, and the spacing between adjacent pits is 1.0-1.4 mm.
[0013] As a further improvement of the present invention, in step S2, the speed of laser etching is 450-550 μm / s.
[0014] As a further improvement of the present invention, in step S3, the 3D printing technology is a fused deposition modeling method.
[0015] As a further improvement of the present invention, the extrusion temperature of the fused deposition modeling method is 210-230° C., and the printing speed is 10-30 mm / s.
[0016] The beneficial effects of the present invention are: 1. The present invention increases the surface roughness of the titanium alloy and forms a micro-texture on its surface through texturing treatment and laser micro-texturing technology, which can increase the contact area between the metal and the polymer PLA, and then combines the 3D printing method to melt the polymer PLA and fill it into the micro-texture, so that the metal and the polymer PLA form an embedded mechanical bond, which can effectively improve the interface bonding strength of the metal-polymer composite structure.
[0017] 2. The present invention controls the line spacing of laser etching within the range of 0.01-0.15 mm, so as to form a certain amount of fine burrs in the micro-texture, thereby increasing the contact area between the metal and the polymer PLA, improving the bonding strength between the metal and the polymer PLA, and avoiding the situation that the inner wall of the micro-texture is too smooth due to too small line spacing, which affects the bonding and fixing effect of the metal and the polymer PLA, or the situation that the burrs are too coarse due to too large line spacing and the depth of the micro-texture is too shallow, which affects the bonding and fixing effect of the metal and the polymer PLA and the subsequent stretching effect of the polymer PLA in the 3D printing process.
[0018] 3. The method of improving the interface bonding strength of the metal-polymer composite structure of the present invention is simple and easy to implement. The experimental process only requires laser etching equipment and does not use any organic reagents. The experimental process is green and environmentally friendly, and can increase the interface bonding strength of the metal-polymer composite structure to 7.1 MPa, and has a wide range of applicable prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of a process for improving the interfacial bonding strength of a metal-polymer composite structure.
[0020] Figure 2 Schematic diagram of microtexture in Example 1.
[0021] Figure 3 Surface morphology of titanium alloy TC4 samples with micro-texture formed on the surface in Examples 1-4 and Comparative Example 1.
[0022] Figure 4 These are the test results of the interface bonding strength of the TC4-PLA composite structures prepared in Examples 1-4 and Comparative Example 1.
[0023] Figure 5 This is a physical picture of the TC4-PLA composite structure prepared in Example 1. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0026] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0027] The present invention takes titanium alloy TC4 as an example to prepare a metal-polymer composite structure and illustrates the technical solution of the present invention.
[0028] Example 1 like Figure 1 As shown, this embodiment provides a method for improving the interface bonding strength of a metal-polymer composite structure, comprising the following steps: S1. Use a wire cutting machine to cut titanium alloy TC4 into specimens with a diameter of 25 mm and a height of 10 mm. Use petroleum ether and anhydrous ethanol to ultrasonically clean the specimens for 120 s each, then take them out and blow dry them with a hair dryer. Then put the specimens into a sandblasting machine and sandblast them for 15 s to obtain titanium alloy TC4 specimens with uniform surface roughening. S2, performing laser etching on the surface of the titanium alloy TC4 sample with uniform surface roughening obtained in step 1, so that a micro texture is formed on the surface of the titanium alloy TC4 sample; S3. Use 3D printing to print polymer PLA material on the surface of titanium alloy TC4 etched with microtexture, so that polymer PLA is filled into the microtexture to form a mechanical bite connection, and obtain a TC4-PLA composite structure.
[0029] Specifically, in step S2, the specific operation of laser etching is: draw a texture array diagram on AutoCAD, cover the surface of the TC4 sample with a diameter of 25 mm, then convert the file into dxf format and copy it into the etcher, and after the etcher is focused and positioned, process the material surface; Figure 2 As shown in the figure, the texture array diagram is a structure in which linear grooves and spherical crown-shaped pits are arranged alternately, the width of the linear grooves and the diameter of the spherical crown-shaped pits are both 50 μm, the spacing between the linear grooves and the adjacent spherical crown-shaped pits is 1.0 mm, and the spherical crown-shaped pits are arranged at intervals parallel to the groove direction, and the spacing between adjacent spherical crown-shaped pits is 1.2 mm. Since the micro-texture is evenly distributed on the surface of the titanium alloy TC4, after the polymer PLA is filled into the micro-texture by 3D printing to form a mechanical bite connection, local stress concentration can be avoided, thereby avoiding deformation or defects on the TC4 surface due to stress concentration, which causes a reduction in the interface bonding strength.
[0030] Among them, the etching power of the etcher is 4 W, the etching speed is 500 μm / s, the line spacing of the laser is 0.01 mm, and the number of scans is 10 times.
[0031] Specifically, in step S3, 3D printing is as follows: using the FDM 3D printing method, the PLA filament is heated, extruded from the nozzle, and sorted and deposited layer by layer according to the planned path and speed to form a cylindrical polymer layer with a diameter of 25 mm and a height of 10 mm on the TC4 surface.
[0032] In this embodiment, the extrusion temperature of FDM 3D printed PLA is 225°C, the printing speed is 16.5 mm / s, the extrusion flow rate is 1.5 r / min, the filling rate is 100%, and the substrate preheating temperature is 60°C.
[0033] Embodiment 2-4 Compared with Example 1, Examples 2-4 adjust the line spacing of the laser in step S2 from 0.01 mm to 0.05 mm, 0.10 mm, and 0.15 mm, respectively. The remaining steps are the same as those in Example 1 and will not be repeated here.
[0034] Comparative Example 1 Compared with Example 1, in Comparative Example 1, the line spacing of the laser in step S2 is adjusted from 0.01 mm to 0.20 mm, and the remaining steps are the same as those in Example 1, which will not be repeated here.
[0035] The morphology of the titanium alloy TC4 samples with micro-texture formed on the surface in Examples 1-4 and Comparative Example 1 was tested. The test results are as follows: Figure 3 shown.
[0036] The TC4-PLA composite structures prepared in Examples 1-4 and Comparative Example 1 were tested for interface bonding strength using an ETM205D microcomputer-controlled electronic universal testing machine in accordance with the national standard GBT 8642-2002. The diameter of the titanium alloy TC4 cylinder and the polymer PLA cylinder was 25 mm and the height was 10 mm; the tensile rate was 100 N / s. The test results are shown in Figure 2. Figure 4 shown.
[0037] like Figure 3 As shown in the figure, when the line spacing of the laser is 0.05 mm, a certain amount of fine burrs are formed in the linear grooves and spherical crown-shaped pits. When the line spacing of the laser is reduced to 0.01 mm, the number of burrs in the linear grooves and spherical crown-shaped pits is significantly reduced, and the smoothness of the bottom surfaces of the linear grooves and spherical crown-shaped pits is significantly improved. At this time, Figure 4 It can be observed that the interface bonding strength of the TC4-PLA composite structure decreases from 7.1 MPa to 1.4 MPa. This may be because as the line spacing decreases, the coverage rate between the spots formed by the laser beam at adjacent positions during scanning increases significantly, which increases the smoothness of the bottom surface of the micro-texture after scanning and reduces the number of fine burrs, resulting in a decrease in the contact area between TC4 and PLA. The reduction in the number of fine burrs will also significantly affect the mechanical bite effect between TC4 and PLA, so that when the laser etching line spacing changes from 0.05 mm (Example 2) to 0.01 mm (Example 1), the interface bonding strength of the TC4-PLA composite structure decreases significantly.
[0038] Depend on Figure 3It can be observed that in Examples 2-4 and Comparative Example 1, when the line spacing of the laser gradually increases from 0.05 mm, the burrs in the linear grooves and spherical crown-shaped pits gradually become thick and round, and the depths of the formed linear grooves and spherical crown-shaped pits gradually become shallower. Correspondingly, the interface bonding strengths of the TC4-PLA composite structure are 7.1 MPa, 4.8 MPa, 2.4 MPa and 0.8 MPa, respectively. That is, when the line spacing gradually increases from 0.05 mm, the interface bonding strength of the TC4-PLA composite structure gradually decreases. This may be because with the increase of the laser etching line spacing, the depth of the formed microtexture gradually becomes shallower, which to a certain extent affects the full stretching of PLA during the printing process. At the same time, the change of the burr morphology formed in the microtexture from long and sharp to short and thick also affects the mechanical bite effect of TC4 and PLA to a certain extent, thereby causing the interface bonding strength of the TC4-PLA composite structure to gradually decrease with the increase of the laser etching line spacing.
[0039] In addition, when the printing speed is in the range of 10-30 mm / s, a complete cylindrical polymer layer with a diameter of 25 mm and a thickness of 10 mm can be obtained. Figure 5 As shown, 5a is the PLA structure obtained by FDM 3D printing in Example 1, and 5b is the TC4 sample with micro-texture etched on the surface. When the FDM 3D printing speed is adjusted to less than 10 mm / s, PLA will form accumulation on the TC4 surface; when the FDM 3D printing speed is adjusted to more than 30 mm / s, loose holes will form in the cylindrical polymer layer, and the density is poor.
[0040] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for improving the interfacial bonding strength of a metal-polymer composite structure, characterized in that: The following steps are involved: S1, performing a texturing treatment on the surface of the titanium alloy to obtain a texturized titanium alloy; S2, performing laser etching on the surface of the roughened titanium alloy obtained in step S1 to form a micro texture on the surface of the titanium alloy, wherein the line spacing of the laser is 0.01-0.15 mm when etching the micro texture; S3. Use 3D printing to print polymer PLA material on the surface of titanium alloy etched with micro-texture, so that polymer PLA is filled into the micro-texture to form a mechanical bite connection, and obtain a metal-polymer composite structure.
2. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 1, characterized in that: In step S1, the texturing treatment is specifically to texturize the surface of the titanium alloy by mechanical sandblasting.
3. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 1, characterized in that: In step S2, the line spacing of the laser etching is 0.05-0.15 mm.
4. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 1, characterized in that: In step S2, the micro texture is a structure in which grooves and pits are arranged alternately.
5. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 4, characterized in that: The width of the groove and the diameter of the pit are both 40-60 μm.
6. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 4, characterized in that: The distance between the groove and the adjacent pit is 0.8-1.2 mm.
7. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 4, characterized in that: The pits are arranged at intervals parallel to the groove direction, and the spacing between adjacent pits is 1.0-1.4 mm.
8. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 1, characterized in that: In step S2, the speed of laser etching is 450-550 μm / s.
9. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 1, characterized in that: In step S3, the 3D printing technology is fused deposition modeling.
10. The method for improving the interface bonding strength of a metal-polymer composite structure according to claim 9, characterized in that: The extrusion temperature of the fused deposition modeling method is 210-230° C., and the printing speed is 10-30 mm / s.
Citation Information
Patent Citations
Method for improving connection strength of thermoplastic composite and metal
CN108297443A
Thermoplastic composite-metal laser welding method
CN113305437A
Titanium alloy workpiece, shell, preparation method of titanium alloy workpiece and etching solution
CN115110139A
3D printing assisted metal-thermoplastic composite laser connection equipment and method
CN117484873A